When Harry Resigns Unexpectedly: An Asynchronous Discussion Role-Play for the Online Management Classroom. (June 2018) - Gibson, Lindsey A.; Ward, Dick; Comer, Debra R.; Rossi, Ken
Management instructors are continually challenged to create learning activities in online courses that duplicate the same opportunities to develop managerial skills afforded to students in traditional face-to-face courses. The purpose of this experiential exercise is to provide online students an opportunity to develop the soft skills all managers need to be successful in the 21st-century workplace. To do this, we use Kolb's learning cycle theory to guide students through an experiential learning exercise. Specifically, an online and updated version of a previously published exercise is developed to facilitate student learning through demonstrating organizational behavior and leadership concepts in a group role-play. Instructors teaching organizational behavior and/or leadership courses at the undergraduate and graduate levels will find this exercise applicable to their classes and teaching portfolio. Teaching notes and instructions for conducting the exercise are outlined. All materials necessary for successfully conducting the exercise are provided as are student reactions to the experience.